2015
DOI: 10.18805/ijar.5579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary esterified glucomannan on performance of broilers exposed to aflatoxin

Abstract: Effect of esterified glucomannan (E-GM), a new generation toxin binder enzymatically extracted from the cell wall of certain stains of Saccharomyces cerevisiae in counteracting the deleterious effects of aflatoxin in broiler chicken was investigated. Broilers fed 1ppm aflatoxin-B1 recorded significantly (P<0.05) poor weekly weight gain, feed consumption, feed efficiency and liveability. Addition of E-GM as a feed additive, in general, in diets free of aflatoxin had no adverse effect on weight gain, feed consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Although there is no study in the literature about the effect of AFB 2 application on weight gain, there are important data on the effects of other aflatoxin species. Similarly to our results, Arvind and Churchil 39 found that there was a 33.94% reduction in weight gain of chickens fed with 1 ppm AFB 1 for 6 weeks. In another study, Dimitri et al 40 reported that exposure to AFB 1 and AFG 2 caused an average of 539 g (16%) body weight loss in rabbits, and this was related to impaired protein synthesis and DNA synthesis.…”
Section: Resultssupporting
confidence: 91%
“…Although there is no study in the literature about the effect of AFB 2 application on weight gain, there are important data on the effects of other aflatoxin species. Similarly to our results, Arvind and Churchil 39 found that there was a 33.94% reduction in weight gain of chickens fed with 1 ppm AFB 1 for 6 weeks. In another study, Dimitri et al 40 reported that exposure to AFB 1 and AFG 2 caused an average of 539 g (16%) body weight loss in rabbits, and this was related to impaired protein synthesis and DNA synthesis.…”
Section: Resultssupporting
confidence: 91%